Associations between size-fractionated particle number concentrations and COPD mortality in Shanghai, China. (1st October 2019) - Yin, Guanjin; Liu, Cong; Hao, Lipeng; Chen, Yichen; Wang, Weidong; Huo, Juntao; Zhao, Qianbiao; Zhang, Yihua; Duan, Yusen; Fu, Qingyan; Chen, Renjie; Kan, Haidong
Abstract: Background: Few studies have investigated respiratory effects of particulate matter air pollution using a full range of particle size distribution. Objectives: To explore the short-term associations between size-fractionated particle number concentration (PNC) and chronic obstructive pulmonary disease (COPD) mortality. Methods: We conducted a time-series study to explore the associations between size-fractionated PNC and daily COPD mortality in the Pudong New Area of Shanghai, China, from 2014 to 2016. We evaluated particle size distribution from 0.01 μm to 10 μm, which was segregated into 7 ranges to better explore the size-dependent associations. We used over-dispersed generalized additive models to estimate the associations after controlling for time trends, temperature, humidity, day of the week and holidays. Results: A total of 5430 deaths due to COPD were identified during the study period. For size ranges from 2.5 – 10 μm, 1–2.5 μm to 0.3–1 μm, there were stronger associations between PNC and COPD mortality, but the associations were statistically insignificant. However, for the smaller size ranges from 0.3 to 0.01 μm, the associations became statistically significant and the magnitude of association remained stable. An interquartile range increase in PNC at lag 0–1 day for size ranges 0.01–0.03 μm, 0.03–0.05 μm, 0.05–0.1 μm and 0.1–0.3 μm was associated with increments of 4.44% (95% CI: 1.16%, 7.73%), 4.31% (95% CI: 1.16%, 7.47%), 4.22% (95% CI: 1.05%, 7.40%), and 4.28% (95% CI: 0.48%, 8.09%) in COPD mortality, respectively. Conclusion: This study suggested that particles below 0.3 μm in diameter might be mainly responsible for the adverse effect of particulate air pollution on CDPD mortality in Shanghai, China. Highlights: A study linking a full range of particle size distribution and COPD mortality. The associations generally increased with smaller particle size. Particles below 0.3 μm in diameter may be mainly responsible for the associations. Particles above 0.3 μm in diameter showed no significant associations.